Bringing Cellular Phone Service to Rural Areas : Grameen Telecom and Village Pay Phones in Bangladesh - Lawson, Cina (World Bank, Washington, DC, 2012)
Grameen Telecom has provided telephone access to nearly 3 million poor villages beyond the reach of the main phone network. The pay phone initiative has benefited from a number of factors: the level of demand for communications in rural areas; the use of the Grameen brand name, facilities, and in-kind support; the large number of Bangladeshis working abroad and wanting to call home; and the country's very high population density. But the initiative has also been held back by problems interconnecting with the network of the incumbent utility and a regulatory framework that has not yet developed the strength and independence to create fair rules of the game for all operators.